2008
DOI: 10.1177/154193120805201969
|View full text |Cite
|
Sign up to set email alerts
|

Simulator Sickness during Head Mounted Display (HMD) of Real World Video Captured Scenes

Abstract: The effect of viewing a display of the "real-world" via an HMD on simulator sickness was investigated. We hypothesized that simulator sickness would increase as time performing a task wearing an HMD increased. Also, we predicted that viewing a "real-world" display via an HMD compared to a control of not using an HMD would result in greater sickness. Participants made 200 head movements to look at eight different objects during two within-subjects conditions: (1) wearing an HMD and viewing a video display of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 5 publications
(20 reference statements)
2
17
0
Order By: Relevance
“…Although common in most VR users, these side effects vary from person to person and, as such, it is difficult to pin down what aspects of immersion are responsible. While some studies suggest that more immersive HMDs are linked to higher levels of sickness in participants [ 53 ], others suggest that there is little difference between the side effects of using standard desktop computer display and a head-mounted VR display [ 54 ]. Regardless, it seems that these symptoms are generally mild and quick to subside and there is some evidence that users can adapt with repeated exposure [ 1 , 55 57 ].…”
Section: Questions About the Use Of Vr In Psychology Researchmentioning
confidence: 99%
“…Although common in most VR users, these side effects vary from person to person and, as such, it is difficult to pin down what aspects of immersion are responsible. While some studies suggest that more immersive HMDs are linked to higher levels of sickness in participants [ 53 ], others suggest that there is little difference between the side effects of using standard desktop computer display and a head-mounted VR display [ 54 ]. Regardless, it seems that these symptoms are generally mild and quick to subside and there is some evidence that users can adapt with repeated exposure [ 1 , 55 57 ].…”
Section: Questions About the Use Of Vr In Psychology Researchmentioning
confidence: 99%
“…The most obvious one to tackle for the sake of user acceptance is that of simulator sickness. There has been research comparing simulator sickness in HMDs versus CAVEs, and some research suggests HMDs have their own unique simulator sickness profile (e.g., Cobb et al, 1999;Moss et al, 2008). If true, this would suggest that each type of VR interface has its own unique sickness considerations, and its own unique way of combating those problems so that they are minimized or eliminated for the users.…”
Section: Discussion and Future Directionsmentioning
confidence: 96%
“…DiZio & Lackner (1997) observed that as latency increased, sickness increased monotonically up to 200 ms. Cobb et al (1999) observed that higher levels of disorientation were experienced when using a slower processor (greater latency). A study by Moss et al (2008) observed that peak sickness was significantly higher when using an HMD and concluded that latency may have been the characteristic that elicited simulator sickness; however, no effort was made to isolate latency as the independent variable, and thus other characteristics may have contributed.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have suggested the following as contributing to simulator sickness: age (Reason & Brand, 1975), gender (Hein, 1993), prior history of simulator sickness (Braithwaite & Braithwaite, 1990), head movement (Moss, Scisco, & Muth, 2008), body movement (Bouyer & Watt, 1996), image scale (Draper et al, 2001), and latency (DiZio & Lackner, 1997), which is the focus of this article. From a physiological perspective, latency with HMDs is the time from user input (head motion) to corresponding feedback (visual perception) of the updated HMD imagery and results in apparent latency that is visually perceived by the user.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation